Multiple Exponential Regression Modeling of Dengue Haemorrhagic Fever Factors in West Java Province, Indonesia - Ridhatusalma, Ghina; Diandra, Salsabila Putri; Rahma, Hasna Nabilah; Pangastuti, Sinta Septi; Roslan, Nurul Farisah Binti (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2024)
Dengue Haemorrhagic Fever is a major public health problem in Indonesia, with 103,509 cases of Dengue Haemorrhagic Fever recorded in Indonesia until the end year of 2020 with 725 deaths with the case fatality rate of 0.70%, and an incidence rate of 38.15 per 100,000 population. The aim of this research is to determine the multiple exponential regression model for the number of Dengue Haemorrhagic Fever cases and its factors in the West Java Province, Indonesia, at the time period of 2020. This research uses secondary data sourced from Open Data Jabar and Badan Pusat Statistik in the form of the number of the Dengue Haemorrhagic Fever cases in each regency or city throughout the West Java, with the independent variables; the number of poverty rate, the number of healthcare workforces, population density, and number of households with adequate sanitation. The final model from the multiple exponential regression shows that population density has a significant effect on the number of Dengue Haemorrhagic Fever cases in the West Java Province.